A place apart? The interventions of John P. Mackintosh and Bernard Crick on Northern Ireland. Issue 4 (2nd October 2017) - Walker, Graham
Abstract: This article considers the significance of the scholarly and practical engagement with the Northern Ireland problem on the part of the Scottish politician and academic John P. Mackintosh, and the academic and controversialist Bernard Crick. It is argued that they were among the few scholars and public figures outside of Northern Ireland for whom the crisis represented an opportunity to explore more searchingly issues with broader significance for the UK as a whole, particularly devolution, and for relations within and between the islands of Britain and Ireland. For both men, Northern Ireland brought into sharp focus questions of sovereignty and identity, and of constitutional reform in the UK.